Can Leader Dark Triad Be Conceptualized as a Moderator? Evidence from a PRISMA Systematic Review - Alowais, Abdelaziz Abdalla; Suliman, Abubakr (Journal of Cultural Analysis and Social Change, 2025)
This research is researching the connection between Ethical Leadership (EL) and Ethical Climate (EC) and the impact of Dark triad (DT) traits on this variable, i.e. narcissism, Machiavellianism, and psychopathy. The research intends to generalize the empirical results and state the contradictions that occur once leaders demonstrate both moral and evil character traits. Systematic Literature Review (SLR) was done according to PRISMA 2020 principles. In searches of Scopus, Web of Science, PsycINFO, and PubMed, 2,137 records were found. When duplicate removal and screening was done, 820 full-texts were evaluated and 196 of them satisfied the inclusion criteria. Bibliographic information, research designs, tools, and results were extracted using data and thematic synthesis was used to recognize recurrent patterns. There was high inter-rater reliability (Cohen Kappa = 0.82), which identifies methodological rigor. Synthesis, the ethical leadership generates ethical climates by setting an example of trust, fairness and accountability. Nevertheless, the relationship is always undermined by DT traits. Narcissists have charisma, but act in personal interest, Machiavellian act so as to manipulate the codes of ethics, and psychopathic foster climates of fear and mistrust. The review singles out the Dark Triad Paradox: leaders at the same time proclaim moral principles, like corporate social responsibility, and also practice manipulation or exploitation and create atmospheres that look strong on the outside, but are weak on the inside. To maintain ethical climates, ethical leadership is needed but not enough. The genuineness and consistency of leaders are vital because the DT traits pervert the ethical cues. The paper develops Social Learning, Upper Echelon, Social Exchange and Paradox Theories and provides both theoretical, empirical and practical contribution. To identify dark tendencies early, organizations and policymakers should have systems in place and scholars need to increase their research on cross-cultural, longitudinal and intervention-based designs.